Selective hydrogenation of 5-HMF to 2,5-DMF over a magnetically recoverable non-noble metal catalyst - Solanki, Bhanupratap Singh; Rode, V. Chandrashekhar (Green Chemistry, 2019)
A non-noble bimetallic catalyst Cu-Fe (1 : 2) was magnetically recoverable, highly selective and efficient for 5-(hydroxymethyl) furfural (5-HMF) hydrogenation to 2,5-dimethyl furan (DMF). The structure-activity correlation was established by characterising the prepared catalyst by XRD, XPS, TEM, ESEM, BET surface area, N-2-adsorption, NH3-TPD, pyridine-IR and H-2-TPR measurements. The high catalytic efficiency was attributed to the oxophilic nature and Lewis acidity of Fe, whereas the selectivity towards DMF was attributed to the Bronsted acidity of CuO and its affinity towards the C-O bond which was further confirmed by NH3-TPD and Py-IR analyses. XPS and XRD revealed the presence of Cu/CuFe2O4 species which catalyzed the hydrogenolysis pathway. TEM and SEM images evidenced the presence of a Cu-Fe nanomorph in which Cu/CuFe2O4 was present. The size of the Cu-Fe nanomorph was found to be between 15.4-17.6 nm. Under the optimised reaction conditions, the highest conversion of 97% and selectivity of 93% were achieved.

Selective oxidation of 5-HMF to DFF over alkali promoted Mn nanocomposite - Solanki, Bhanupratap Singh; Roh, Hyun-Seog; V. Rode, Chandrashekhar (Applied Catalysis A-General, 2023)
Various compositions of Cs promoted Mn catalysts were synthesized and investigated for selective oxidation of 5HMF to DFF, among which Mn-Cs(80:20) was found to be most efficient giving 91 % conversion of 5-HMF and 99 % selectivity to DFF. Detail characterization like N2-sorption, BET surface area, TG-DTA, XRD, XPS, FE-SEM-EDX, TEM, HR-TEM, CO2-TPD, H2-TPR, O2-TPO, FTIR, Raman spectra and CH3OH-IR were done to establish structureactivity correlation. Enhanced surface area, porosity, thermal stability, dual morphologies were observed due to inclusion of Cs in Mn lattice domain which further enhanced the crystallinity, and oxygen diffusion on the surface. Mixed morphologies comprising nanoparticles (4-5 nm) and nanocubes (50-60 nm) were observed with enhanced redox potential and reduced work function due to weakening of Mn-O bonds. Significant increase in the basicity of catalyst, interfacial redox properties and lattice oxygen led to highly efficient oxidation of 5-HMF to DFF via Mars-van Krevelen mechanism at relatively milder conditions i.e. T = 90 degrees C and PO2= 200 psig. The catalyst was easily recyclable up to 7 times with minor loss in activity which was regenerated heat treatment protocol.
Keywords: 5-HMF; Biomass; heterogeneous catalyst; polyurethane; Selective oxidation

Highly efficient, co-solvent assisted glycolytic depolymerization of waste polyethylene terephthalate (PET) into Bis(2-hydroxyethyl) terephthalate (BHET) monomer - Markandeya, Nishant; Solanki, Bhanupratap Singh; Ramalingam, Karthick; Kamble, Sanjay (Industrial & Engineering Chemistry Research, 2025)
Recently, growing use of plastics has led to the accumulation of waste that must be dealt with paramount priority. Among all plastic wastes, polyethylene terephthalate (PET) is the most widely used thermoplastic polyester globally because of its extensive applications in packaging, automotive manufacturing, and textile markets. Thus, there is a need to develop a sustainable and viable PET recycling process. This study presents an efficient solvothermal process for the depolymerization of PET into bis(2-hydroxyethyl) terephthalate (BHET) using co-solvent assisted glycolysis. The process uses N-methylimidazole (NMI) as a cosolvent with ethylene glycol (EG), achieving complete PET conversion and 92% BHET yield under optimized reaction conditions (180 degrees C, 45 min, PET:EG:NMI ratio of 1:7:8) without using a catalyst. The effectiveness of the cosolvent system was attributed to its polarity and H-bonding capabilities, which enhanced polymer swelling and facilitated the depolymerization. SEM analysis revealed pore formation in the NMI-treated PET, whereas FTIR studies confirmed the progressive formation of ester groups during depolymerization of PET. Kinetics studies based on different models indicated that, at higher temperatures, the surface reaction and homogeneous model proved to be rate-controlling due to the elimination of mass transfer limitations. A preliminary technoeconomic analysis and recyclability experiments further supported the scalability potential of the present study.